Discounts and price discrimination in the Telecommunications Regulation of NGA Networks - Martin Lundborg; Ernst-Olav Ruhle; Christian Bahr (International Telecommunications Society (ITS), 2010)
While the economic theories have come to the conclusion that discounts and price discrimination are enhancing welfare, an obligation to offer non-discriminatory prices has been implemented in the sector specific regulation for telecom operators enjoying SMP. Moreover, price discrimination has generally been accepted in competition law cases. This might change in the future as the EU Commission has published the draft recommendation for the regulation of Next Generation Access networks (NGA). In this draft recommendation, the EU proposes to allow for the introduction of discounts (price discrimination) in certain cases related to Next Generation Access (NGA) networks on the wholesale level. This paper looks at the implications of an acceptance of price discrimination in the sector specific regulation of telecommunication markets. We conclude that price discrimination is expected to be effective in creating incentives for investments in NGA networks, but that there is a risk that price discrimination will harm competition which in turn might imply negative welfare effects. Therefore, a case-by-case analysis instead of a general approach is required.
Keywords: 330